Workplace Noise Pollution and It's Correlation with Hypertension: A Meta-Analysis - Muna Maimunah Salsabila; Bhisma Murti; Sumardiyono Sumardiyono (Journal of Epidemiology and Public Health, 2022)
Background: Noise is identified as one of the most widespread physical factors in occupational health and safety (OHS) and is a problem in all regions of the world. Noise can be pathogenic if there is continuous and repeated exposure causing a persistent upregulation of vascular autoregulation resulting in hypertension. Epidemiological studies report an association between occupational noise exposure and hypertension. This study aims to determine the effect of noise exposure in the workplace on hypertension.Subjects and Method: This study is a systematic review and meta-analysis with the following PICO, Population= workers, Intervention= occupational noise exposure ≥85 dBA, Comparison= occupational noise exposure <85 dBA, Outcome= hypertension. The meta-analysis was carried out using search articles from databases such as Google Scholar, PubMed, and Science Direct, published from 2012 to 2022. The keywords used in the article search were “Occupational Noise Exposure” OR “Occupational Noise” AND “Hypertension” OR "High Blood Pressure" OR "Primary Hypertension" AND "Workers" AND "Cross-Sectional Study". The included studies were full-text articles published in English, reporting the adjusted odds ratio (aOR) of the results of the multivariate analysis, and the study design was cross-sectional. The selection of articles was carried out using PRISMA flow-charts and analyzed using the Revie Manager 5.3 application.Results: A total of 10 cross-sectional studies were analyzed involving 12,437 workers covering Iran, Jordan, China, Indonesia, Tunisia, and Brazil. The results of the meta-analysis showed that workers exposed to noise 85 dBA had higher hypertension than workers exposed to noise <85 dBA (aOR= 1.96; 95% CI= 1.68 to 2.29; p< 0.001).Conclusion: Exposure to occupational noise ≥ 85 dBA increases hypertension compared to exposure to occupational noise <85 dBA. Keywords: occupational noise, noise exposure, hypertension, meta-analysis Correspondence:Muna Maimunah Salsabila. Masters’ Program in Public Health, Universitas Sebelas Maret, Jl. Ir. Sutami 36A, Surakarta 57126, Central Java, Indonesia. Email: munamaimunahs@gmail.com. Mobile: +6285728565926.